Impact of psychological contract breach and ethical leadership on turnover intention: Emotional exhaustion as mediator - Ivana, Priska Riafinola; Marumpe, Dody Pratama; Daud, Ilzar; Yakin, Ikram (Institute of Computer Science (IOCS), 2025)
This study analyses the influence of psychological contract breach and ethical leadership on employee Turnover Intention, with emotional exhaustion as a mediator, in the Indonesian state-owned banking sector, including Bank Mandiri, Bank Rakyat Indonesia (BRI), Bank Negara Indonesia (BNI), and Bank Tabungan Negara (BTN). The approach used is quantitative with associative methods, and data analysis using Structural Equation Modeling (SEM) with AMOS 26 software. Data were collected through a Google Form questionnaire with a Likert scale of 1-5 from 206 employees who met specific criteria: Respondents are Indonesian citizens, Respondents work at state-owned banks (Bank Mandiri, BRI, BNI, BTN) in Indonesia, Respondents are still actively working, and Respondents have a minimum work period of one year at the bank. The results showed that psychological contract breach significantly positively affects emotional exhaustion, which impacts Turnover Intention. On the other hand, ethical leadership was shown to affect emotional exhaustion and turnover intention significantly negatively. Although psychological contract breach does not significantly affect turnover intention, emotional exhaustion is a mediator, linking psychological contract breach and ethical leadership with turnover intention. This study provides insights for Indonesia's state-owned banking sector into the factors that influence employee turnover intention, as well as helping to develop more effective employee retention strategies, thereby enhancing workforce stability and, in turn, supporting economic growth through improved performance.